The contact pressure analysis of different load and diameter ratio on hemispherical contact: biomechanical perspectives / M. Danny Pratama Lamura ... [et al.] - Lamura, M. Danny Pratama; Achmad, Cucu Bachtiar; Ammarullah, Muhammad Imam; Maula, Mohamad Izzur; Husaini, Farhan Ali; Bayuseno, Athanasius Priharyoto; -, J. Jamari; Hidayat, Taufiq (UiTM Press, 2024)
Contact mechanics is pivotal in understanding interactions between surfaces, particularly in biological contexts and the human body. When surfaces come into contact, the roughness represented by microscopic peaks called asperities becomes crucial. In this study, spherical contact modeling is explored, which is an extensively researched area in both engineering and biomechanics. By examining hemispherical contact systems, valuable insights into their biomechanical response are gained. Specifically, the investigation focuses on how geometric variations and applied loads impact contact pressure using finite element analysis. The model comprises two hemispheres with varying diameter ratios. The results show higher diameter ratios increase maximum contact pressure and expand the pressure contour distribution. While M1 shows similar pressure distribution in both hemispheres under additional load, M2 and M3 exhibit a broader distribution in the bottom hemisphere compared to the upper. Consequently, lower diameter ratios emerge as safer design choices, whereas higher ratios require careful load management to prevent failure.